Atividade antimicrobiana dos extratos de Schinus terebinthifolia Raddi - Rebello, Luciana Camizão (2013)
The Schinus terebinthifolia Raddi, popularly known as pepper tree, is in the National Medicinal Plants of the SUS’s Interest List and has great potential for growth inhibition of microorganisms, which makes this an alternative to medicinal plant antimicrobial activity. This study aims to evaluate the antimicrobial activity against pathogenic fungi (Colletotrichum gloeosporioides Penz and Colletotrichum musae) and against the bacteria which causes human infection (Staphylococcus aureus), from the extracts fractions obtained from leaves and stem bark of S. terebinthifolia, to identify secondary metabolic compounds in leaves and stem bark and quantify the compounds of the flavonoids group. The extractions of leaves and stem bark were prepared by maceration using increasing polarity solvents (hexane, dichloromethane and ethanol) and ethanol solvent for the preparation of crude extract that underwent liquid-liquid cut. The phytochemical screening of crude ethanol extracts of both parties and the quantification of flavonoids were performed. The fractions were tested for determining the minimum inhibitory concentration for bacteria and for mycelial growth inhibition of the fungus. The results showed that all tested microorganisms demonstrated sensitivity to the compounds found in the extracts of S. terebinthifolia regardless the type of extraction, and that the flavonoids are found in greater amounts in the leaves (52,93 µg.mL-1) than in the stem bark (9.58 µg.mL-1), possibly, together with tannins, they do the inhibitory activity of fungi and bacteria. Therefore, extracts of bark stem and leaves of the pepper tree may be a good way for controlling the growth of these pathogen and they can act as an herbal medicine with antibiotic effect as well as being a possible agent to control the diseases in papaya and banana plants.